2020
DOI: 10.1021/acsomega.0c05033
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Surfactant- and Cosurfactant-Aided Pine Oil Nanoemulsions by Isothermal Low-Energy Methods for Anticholinesterase Activity

Abstract: Highly stable pine oil-loaded nanoemulsions were evaluated for nutraceutical and storage stability applications. Pine oil-loaded nanoemulsion preparation was done with pine oil as the oily phase and additionally with different ratios of the non-ionic surfactant (Tween 80) and cosurfactant (ethanol) in an aqueous solution using the isothermal lowenergy or spontaneous emulsification method. A transparent and stable nanoemulsion was obtained with a combination of pine oil (5 wt %), surfactant mixture (35 wt %), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 50 publications
0
17
0
1
Order By: Relevance
“…The previous study of the Tween 80 and PEG 400 combination in nutmeg oil showed stable microemulsion especially on physical and antioxidant activity within 6 cycles (Shabrina et al, 2021). The Tween 80 has long-chain fatty acid and are available to decrease the interfacial tension between the nutmeg oil and cosurfactants, which provides clear Microemulsion (Handa et al, 2021). The PEG 400 molecule has two parallel helical bonds that form molecular complexes with active substances and cosurfactants in a circular chain formation to form intramolecular dispersions that can maintain stability of drug molecules (Seo et al, 2020).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The previous study of the Tween 80 and PEG 400 combination in nutmeg oil showed stable microemulsion especially on physical and antioxidant activity within 6 cycles (Shabrina et al, 2021). The Tween 80 has long-chain fatty acid and are available to decrease the interfacial tension between the nutmeg oil and cosurfactants, which provides clear Microemulsion (Handa et al, 2021). The PEG 400 molecule has two parallel helical bonds that form molecular complexes with active substances and cosurfactants in a circular chain formation to form intramolecular dispersions that can maintain stability of drug molecules (Seo et al, 2020).…”
Section: Resultsmentioning
confidence: 91%
“…The PEG 400 molecule has two parallel helical bonds that form molecular complexes with active substances and cosurfactants in a circular chain formation to form intramolecular dispersions that can maintain stability of drug molecules (Seo et al, 2020). Both Tween 80 and PEG 400 could protect active ingredients from thermal and light exposure so that the microemulsion activity would be as stable as the physical appearance (Handa et al, 2021;Lv et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Alcohols with short and medium chain hydrocarbons are usually incorporated as co-surfactants during the formulation of nanoemulsions to lower the concentration of surfactants. 43 Additionally, the partitioning of these co-surfactants be Tween oily and aqueous phases can decrease the interfacial tension and permit higher miscibility of the two phases. 44 Hence, ethanol, isopropyl alcohol and propylene glycol were chosen as co-surfactants and mixed at a fixed ratio with Tween 80 (1:1 w/w).…”
Section: Resultsmentioning
confidence: 99%
“…Peran tween 80 sebagai surfaktan dan PEG 400 sebagai ko-surfaktan dapat mempengaruhi hasil akhir nilai ukuran partikel pada nanoemulsi. Surfaktan akan teradsorpsi pada permukaan droplet fase minyak dan akan membentuk misel yang dapat menurunkan tegangan antarmuka sehingga menghasilkan nanoemulsi yang baik dengan ukuran partikel yang kecil 15 . Ko-surfaktan akan membantu dalam mencegah terjadinya pemisahan fase agar tidak bergabung kembali 16 .…”
Section: Ukuran Partikelunclassified